Evaluation of new kits for the assessment in vitro of thyroid function by determination of serum total thyroxine, free TBG capacity, and free thyroxine index using Sephadex G-25 and (125)I-labelled triiodothyronine and thyroxine - Howorth, P. J. N. (1974)
A trial was carried out on 134 patients of new kits (Ames Co) using columns of Sephadex G-25 for the determination of serum total thyroxine (Tetralute test) and for the indirect estimation of serum free thyroxine-binding globulin capacity (Trilute test). Both new methods were quicker and easier than the reference resin methods and of similar precision. The two measurements when combined to give a free thyroxine index (Trilute-Tetralute-FTI) increased further the diagnostic discrimination and usefulness of the tests. The method for the determination of serum thyroxine can be modified to give a direct estimate of serum free thyroxine, expressed as a free thyroxine index. This new single-column technique, called the `single-column free thyroxine index', gave a good correlation with clinical thyroid status in a preliminary trial of 45 patients.